The Analysis of Generic Structures and Copy Elements in Online Shop Video Advertisements - Cut Ansi Faradhiba Hayati (Passage, 2018)
In this era of advance information and technology, many e-commerce platforms are rising and competing to attract the prospect customers by creating unique and out of the box video advertisements. Among them are Bukalapak, JD.ID, Lazada, Shopee, and Tokopedia as the top five rising e-commerce platforms in Indonesia which place their video advertisements in YouTube. The objectives of this research are to identify the realization of the generic structure elements in the video advertisements of those five mentioned online shops and how copy elements are distributed in the generic structure of each video. Genre analysis under the theory of Systemic Functional Linguistics by M.A.K Halliday (1984) are utilized as the framework of the analysis to see the generic structure of each video advertisement, and copy elements theory proposed by Maslen (2009) are used to identify the copy elements. The needed data were mainly taken from each online shop's YouTube channel which were further transcribed and put into designed table. This study applies qualitative approach and employs simple descriptive statistics analysis to help mapping out the findings regarding the generic structure of the video advertisements and the copy elements distribution. Keywords: e-commerce, online shop, generic structure, copy element, Systemic Functional Linguistics